Analisis Efektivitas Penyaluran Zakat pada Rumah Zakat - Efri Syamsul Bahri; Zainal Arif (Prodi Perbankan Syariah FAI UMT, 2020)
Rumah Zakat is a philanthropic institution that manages zakat and infaq/alms with an average amount of zakat and infaq/alms collection for 5 (five) years from 2015-2019 amounting to IDR176,298,735,332.80, and the average amount of distribution for 5 (five) years for the period 2015-2019 amounting to IDR152,627,321,395.80. The problem in this research is how is the effectiveness of zakat distribution and charity/alms house? The purpose of this study was to measure the effectiveness of the distribution of zakat and donations/charity at the Rumah Zakat. This research uses a literature study and quantitative method with the Allocation to Collection Ratio (ACR) ratio measurement model based on Zakat Core Principle (ZCP). The object used in this study is the financial statements of the Rumah Zakat for the period of 2010 to 2019. The results of the study show that distribution includes 8 asnaf, namely: fakir, miskin, Amil, Muallaf, Riqob, Ghorimin, Ibnu Sabil, and Fii Sabilillah, in four groups empowerment namely: Healthy Smiles, Champion Smiles, Independent Smiles, and Sustainable Smiles with an Integrated Community Development (ICD) approach that is aligned with the Millennium Development Goals (MDGs). Based on ZCP the effectiveness of distribution for 5 years of operation is 87% or included in the Effective category, where the Alocation to Collection Ratio (ACR) reaches 70-89%. That is, zakat and donation/alms are channeled to mustahik effectively. Suggestion from this research is that Rumah Zakat can increase the effectiveness of zakat distribution with an effectiveness level above 90% so that it is included in the Highly Effective category if ACR ≥ 90 percent)